FILSAFAT ISLAM SEBAGAI PARADIGMA ISLAMISASI PSIKOLOGI - Ihsan, M. Alim (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Islamic philosophy as a paradigm of Islamic psychology can be grasped as an effort of psychology islamization employing Islamic philosophy as its pattern. In other words, current psychology should be Islamized as a reference to develop current psychology into Islamic psychology. This article discusses Islamic philosophy from its growth and development in Islamic worldKata Kunci: Filsafat Islam, islamisasi psikologi